Investigating Fluidisation of Powder in the Supply Bins of Polymer Laser Sintering Machines Using Foundational 2D Numerical Modelling - Mwania, Fredrick; Maringa, Maina; Walt, Jacobus van der (Journal of Research Updates in Polymer Science, 2026)
Fluidisation is a critical process in polymer laser sintering, but limited studies have been conducted in this area. In this regard, two-dimensional numerical models were used, in this study, to establish a suitable flowrate and period of fluidization for a polypropylene powder material used as a feedstock in polymer laser sintering. The study also investigated the impact of different spreading parameters and properties of material such as, bulk-density, particle-size, and fluidised bed height, on the fluidisation behaviour of powder in the supply bins of EOS P380, P385, and P396 machines. A computational fluid dynamic (CFD) software, Fluent, was identified and applied to investigate the fluidisation behaviour of a polypropylene material. The results arising from the numerical modelling revealed that the suitable fluidisation-flowrate for the material considered is 20 liters/min and the period lies between one and three seconds. It was also established that it might be difficult to fluidise polymeric materials with a density equal to or greater than 1500 kg/m3, particle sizes equal to or greater than 90 µm, and for bed heights below 0.10 m.